Determining Stingless Bee Honey Adulteration with Cane Sugar using Fiber Optic Lateral Offset Method - Harun, Muhammad Wahyu; Adnan, Nurul Nadia; Mohd Yusoff Shah, Nurul Ain (Enhanced Knowledge in Sciences and Technology, 2025)
This study aims to lay the groundwork for utilizing a fiber optic lateral offset system to detect adulteration in stingless bee honey, addressing the limited research available on this technique. The focus is to design and test the fiber optic lateral offset system, evaluate its performance with honey samples of varying purity levels, and analyse its effectiveness in detecting adulteration. Tests were conducted using cane sugar-adulterated honey samples at offset distances ranging from 0.0 µm to 5.5 µm. The system demonstrated promising sensitivity, achieving the highest accuracy at a 0.0 µm offset (-1.467 dBm/mol) and reliable performance at larger offsets, such as -1.193 dBm/mol at 5.5 µm. Compared to refractometer measurements, the fiber optic system proved more effective in identifying subtle adulteration. This study serves as a foundation for developing cost-effective, real-time, and portable sensors for honey quality assurance and broader food authenticity applications.